Pembahasan Literatur pada Makanan dalam Perspektif Islam dan Kesehatan Kepada Mahasiswa Farmasi Universitas Aufa Royhan Di Kota Padangsidimpuan - Pasaribu, Heka Afriannur (Universitas Aufa Royhan, 2023)
To maintain its survival, humans need food as the most basic thing. But still it must be considered of optimal nutritional value in the food. Food consumed by humans must contain various kinds of nutrients which can support the process of human life. The degree of public health can be optimally increased by the provision of hygienic and halal food, this fulfills good food criteria in Islamic and health perspectives. This study used the literature review method where the researcher conducted a series of studies involving various kinds of information derived from literature such as books, encyclopedias, documents, etc. with the aim of finding various kinds of theories and ideas which could then be formulated according to the research objectives. Research results from various literature sources indicated that Islam has arranged in such a way both in the Qur'an and Hadith regarding food. Islam and Health go hand in hand in maintaining human survival through healthy food, halal and thayyib. Islam and health basically have the same goal for the good of humans. Therefore, in eating food there are several conditions that must be fulfilled and truly considered so that humans avoid various types of diseases sourced from food. Keywords: food, Islam, health, nutrition, halal.